2011
DOI: 10.4049/jimmunol.1101871
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Repertoire Development in Fetal and Neonatal Piglets. XX. B Cell Lymphogenesis Is Absent in the Ileal Peyer’s Patches, Their Repertoire Development Is Antigen Dependent, and They Are Not Required for B Cell Maintenance

Abstract: The continuous ileal Peyer’s patches (IPP) of sheep are regarded as a type of mammalian bursal equivalent where B cells diversify their repertoire in an Ag-independent fashion. Anatomically and developmentally similar IPP occur in swine. Resection of ∼90% of the IPP in piglets at birth did not alter Ig levels in serum and secretions or retard diversification of the Ab repertoire when animals were maintained in isolators and colonized with a defined gut flora. Resection or sham surgery elevated IgG and IgA in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
15
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 67 publications
(118 reference statements)
5
15
0
Order By: Relevance
“…These investigators found that resection of the sheep IPP resulted in a prolonged B cell deficiency, although this deficiency did not alter serum Ig levels (49). The latter is consistent with our findings (39). It is possible that this discrepancy could be methodological since evidence for B cell deficiency in lambs with resected IPP was based on manual counting of limited numbers of Ig + B cells using a slide smear method (17) that can generate a significant error.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…These investigators found that resection of the sheep IPP resulted in a prolonged B cell deficiency, although this deficiency did not alter serum Ig levels (49). The latter is consistent with our findings (39). It is possible that this discrepancy could be methodological since evidence for B cell deficiency in lambs with resected IPP was based on manual counting of limited numbers of Ig + B cells using a slide smear method (17) that can generate a significant error.…”
Section: Discussionsupporting
confidence: 81%
“…The shift from the fetal to the adult type of lymphocyte distribution and its dependence on degree of colonization indicate that events in the IPP proceed in an Ag-dependent manner, as in secondary lymphoid tissues. This conclusion is supported by findings that the shift is also accompanied by an increase in Ab repertoire diversification (39) (Fig. 2), which also characterize secondary lymphoid tissues (31,33,34).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…However, pigs, together with all other ungulates, were speculated for .30 y to belong to species that use ileal Peyer's patches for development of B cells (10,11,25). We have previously shown that ileal Peyer's patches are not required for B cell development and maintenance (12)(13)(14), and that this role has probably been filled by the BM (26)(27)(28)(29)(30). In the present study we have finally shown that B cell lymphogenesis in pigs clearly occurs in the BM.…”
Section: Discussionsupporting
confidence: 51%
“…These species use specialized GALTs located in a hindgut, and include gallinaceous birds that use the bursa of Fabricius, rabbits that use the sacculus rotundus, and ungulates, including swine, that use ilealthis categorization by showing that at least in swine (and probably in other ungulates), ileal Peyer's patches are not a significant source of B cells, are not required for maintenance of the systemic B cell pool, and are not a site of primary B cell lymphogenesis (12)(13)(14). The results of the present study extend those studies by showing that porcine B cells are developed throughout life in the BM, the primary lymphoid organ also for mice and humans (2,3).…”
mentioning
confidence: 99%